Los plaguicidas y su impacto en el medio ambiente. - Belitama Montero, Fernanda Beatriz (2022)
The use of pesticides are chemical products most used by man, they have been used above all to combat crop pests. Its excessive use leads to environmental pollution and human health. For their part, pesticides, especially organophosphates, organochlorines and carbamates (agrochemicals with the greatest environmental impact) and chemical fertilizers that have caused eutrophication, water toxicity, groundwater contamination, air pollution, soil and ecosystem degradation, biological imbalances and reduction of biodiversity; Said environmental contamination is given fundamentally by direct applications in agricultural crops, inadequate washing of container tanks, leaks in storage tanks and waste discharged and disposed of on the ground, accidental spills, the inappropriate use of the same by the population. This present research work is carried out with the purpose of publicizing the impact of the use of pesticides on the environment, consulting bibliographic sources. Pesticides have become a threat to the environment due to their high degree of toxicity.